SEEING THROUGH LANGUAGE - Collins, Anthony (PINS-Psychology in Society, 2025)
Tuffin, K (2005) Understanding critical social psychology. London: Sage. ISBN 0-7619-5497-X (pbk). Pages 204. Keith Tuffin’s book comes as part of a recent wave of books designed as usable textbooks for courses in Critical Social Psychology. As an emerging area, there is still no final consensus on what exactly constitutes the core curriculum in this field, but there is an acknowledged need for student-friendly texts that are accessible to advanced undergraduates who are not quite ready for the more arcane primary publications in which the theories and debates of this sub-discipline have been thrashed out. It follows in the very recent tradition of Gough & McFadden’s (2001) Critical social psychology: An introduction, and Hepburn’s (2002) Introduction to critical social psychology, while providing a significantly different slant to either of these works.